An empirical analysis of Swedish government bond yields - Tanweer Akram; Mahima Yadav (Levy Economics Institute of Bard College, 2024)
This paper econometrically models the dynamics of Swedish government bond (SGB) yields. It examines whether the short-term interest rate has a decisive influence on long-term SGB yields, after controlling for other macroeconomic and financial variables, such as consumer price inflation, the growth of industrial production, the stock price index, the exchange rate of the Swedish krona, and the balance sheet of Sweden's central bank, Sveriges Riksbank. It applies an autoregressive distributive lag (ARDL) approach using monthly data to model SGB yields across the Treasury yield curve. The results of the estimated models show that the short-term interest rate has a marked influence on the long-term SGB yield. Such findings reaffirm John Maynard Keynes's view that the central bank's monetary policy affects long-term government bond yields through the current short-term interest rate. It also shows that the interest rate behavior observed in Sweden is in concordance with empirical patterns discerned in previous studies related to government bond yields in both advanced countries and emerging markets.
Keywords: E43; E50; E58; E60; G10; G12; 330; Swedish Government Bonds; Bond Yields; Short-term Interest Rate; Inflation; Sveriges Riksbank; Sweden